PsycEXTRA Dataset 2011
DOI: 10.1037/e512592013-516
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous online tracking of adjacent and nonadjacent dependencies in statistical learning

Abstract: When children learn their native language, they have to deal with a confusing array of dependencies between various elements in an utterance. Some of these dependencies may be adjacent to one another whereas others can be separated by considerable intervening material. Research on statistical learning has begun to explore how such adjacent and nonadjacent dependencies may be learned-but in separate studies. In this paper, we investigate whether both types of dependencies can be learned together, similarly to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Studies in which participants are either tested multiple times after multiple familiarization sessions or in which on‐line learning measures are collected (such as the AGL‐SRT task developed by Misyak et al., ) could be used to reveal individual learning trajectories. One recent study did employ this paradigm to test learning of a language containing both adjacent and non‐adjacent dependencies (Vuong, Meyer, & Christiansen, ). Consistent with the results of the current studies, they found that learners were sensitive to both types of dependencies from early in familiarization, though a long exposure duration was needed to reveal significant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in which participants are either tested multiple times after multiple familiarization sessions or in which on‐line learning measures are collected (such as the AGL‐SRT task developed by Misyak et al., ) could be used to reveal individual learning trajectories. One recent study did employ this paradigm to test learning of a language containing both adjacent and non‐adjacent dependencies (Vuong, Meyer, & Christiansen, ). Consistent with the results of the current studies, they found that learners were sensitive to both types of dependencies from early in familiarization, though a long exposure duration was needed to reveal significant effects.…”
Section: Discussionmentioning
confidence: 99%
“…52 Several studies with infants and adults have shown categorization of novel words when these words are embedded in frame contexts giving credence to both frame and flexible frame proposals of lexical Volume 4, September/October 2013 category acquisition. 8,9,53,54 However, it is difficult to determine whether learning in these studies is the result of adjacent or nonadjacent dependency learning or both.…”
Section: Nonadjacent Dependencies and Lexical Categoriesmentioning
confidence: 99%
“…If true, this would suggest a severe limitation in learners' ability to track adjacent and nonadjacent statistics concurrently (see also Pacton & Perruchet, 2008). Romberg and Saffran (2013) investigated whether adjacent and nonadjacent dependencies can be learned concurrently or whether there may be trade-offs between adjacent and nonadjacent learning (see also Vuong, Meyer, & Christiansen, 2011). Similar to Gómez (2002), they trained adult learners on an AxB grammar with deterministic nonadjacent dependencies between the first and third elements (three A-B frames, p = 1.0 each).…”
Section: Concurrent Statistical Learning Of Adjacent and Nonadjacent mentioning
confidence: 99%